Mewujudkan Independensi Hakim melalui Reaktualisasi Behavioral Jurisprudence pada Pasal 65 Undang-Undang Nomor 1 Tahun 2023 : Mewujudkan Independensi Hakim melalui Reaktualisasi Behavioral Jurisprudence pada Pasal 65 Undang-Undang Nomor 1 Tahun 2023 - Amanda Sheilla Rahma Zahbrita; Fatika Az Zahra Khairunnisa; Rizal Surya Handika; Salma Fitriya Nur Hanifah (Judex Laguens, 2025)
The law functions to maintain public interests in society, safeguard human rights, and realise justice. Judges as the enforcers of justice have independence and self-reliance in every law enforcement process that is guaranteed in the legislation. Unfortunately, the independence of judges is often limited by the law itself and does not provide a gap for judges to include elements of behavioural jurisprudence and their conscience. This research aims to elaborate the urgency of behavioural jurisprudence in criminal law enforcement by judges. This research can be useful as an evaluation material in solving the problem of overcapacity in correctional institutions in Indonesia. The research method used in this research is normative legal research method with case approach and legislation. The results of the research show that the reform of the punishment system by prioritising behavioural jurisprudence and the conscience of judges will ensure the spirit of law enforcement that prioritises benefit and justice.